Inhibition of autophagy augments the anticancer activity of α-mangostin in chronic myeloid leukemia cells. Issue 3 (March 2014) - Chen, Jia-Jie; Long, Zi-Jie; Xu, Dong-Fan; Xiao, Ruo-Zhi; Liu, Ling-Ling; Xu, Zhi-Fang; Qiu, Samuel X.; Lin, Dong-Jun; Liu, Quentin
Abstract Natural products possessing anticancer activity have been extensively studied because of their low toxicity and potential effect. α-Mangostin, a component of Garcinia mangostana Linn, is a xanthone derivative shown to have antioxidant and antitumor properties. This study was carried out to investigate how to improve the anticancer effects of α-mangostin in chronic myeloid leukemia (CML) cell lines bearing wild-type BCR–ABL or BCR–ABL-T315I mutation. We showed that α-mangostin inhibited cell proliferation of K562, KBM5 and KBM5-T315I cells in both a time- and dose-dependent manner. Significantly, α-mangostin increased the number of apoptotic cells and induced DNA fragmentation compared to control cells. Moreover, α-mangostin selectively inhibited proliferation in primary CML cells, while showing limited lethality in normal hematopoietic progenitors. Additionally, α-mangostin induced not only apoptosis but also autophagy in CML cells. α-Mangostin dramatically increased the expression levels of LC-3II, an autophagosome marker in mammals, and the accumulation of autophagic vacuoles (AVs). Inhibition of autophagy by chloroquine enhanced α-mangostin-mediated cytotoxicity through increasing apoptosis. Taken together, our data suggest that targeting the autophagy pathway is a promising therapeutic strategy to enhance α-mangostin-induced apoptosis. Our study provides an approach for future studies to explore this combination for the treatment of CML.